Screening of Proteolytic Enzymes of Streptomyces sp. Local Strain and Their Characterization - DERI YURATMOKO; NISA RACHMANIA MUBARIK; ANJA MERYANDINI (Microbiology Indonesia, 2007)
Protease of two Streptomyces sp. strain were chosen for characterization because of the large clear zone surrounding the colony in nutrient agar media containing 1% (w/v) skim milk. Extracellular protease from the two isolates SLW 8-1 and 45I-3 were characterized following incubation of the isolate in Nutrient Broth media containing skim milk or chicken feather (1%). The optimum activity of the protease SLW 8-1 was at pH 9 and 80 ºC, whereas that of the keratinase was at pH 6.5 and 70 +C. Protease of strain 45I-3 showed its optimum activity at pH 7.5 and 50 ºC whereas the keratinase was at pH 8.5 and 80 ºC.